Classroom Management Information Technology - Mohammad Syahidul Haq (EDUCATIO : Journal of Education, 2017)
Development of Information Technology in the field of education today can not be avoided. In the learning process is now not limited to space and time with the presence of information technology. To realize quality of learning, information technology is one aspect of classroom management. Many strategies are offered in classroom management To realize learning objectives. E-learning is a solution in the management of information technology-based classes are much used in various educational institutions. With many advantages, e-learning supports virtual-based learning process.